2020
DOI: 10.1111/phpp.12566
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab for the treatment of chronic actinic dermatitis

Abstract: Dupilumab for the treatment of chronic actinic dermatitis 1 | INTRODUC TI ON Chronic actinic dermatitis (CAD) is an immune-mediated photodermatosis characterized by chronic, pruritic, eczematous, and often lichenified plaques distributed primarily upon sun-exposed skin. 1 The pathophysiology is believed to involve a delayed-type hypersensitivity reaction to an endogenous, photoinduced, cutaneous antigen, which has been speculated to be DNA. 1 First-line management options include strict photoprotection, topica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…Furthermore, in the literature review, we identify three reports with a total of 10 patients ( 8 10 ). All the patients showed a moderate-to-complete reduction in disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the literature review, we identify three reports with a total of 10 patients ( 8 10 ). All the patients showed a moderate-to-complete reduction in disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…All the patients showed a moderate-to-complete reduction in disease severity. Two patients developed conjunctivitis and were successfully treated with ophthalmic corticosteroids (20% of the cases) ( 8 ). Only one patient had to suspend the treatment with dupilumab because of the DFR (dupilumab facial redness).…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 9 However, these treatments are not so effective in most patients with severe CAD; thus, thalidomide, colostrum-macrophage-activating factor, and biotherapy (tofacitinib and dupilumab) have been proposed to be particularly beneficial in improving outcomes in these cases. 4–6 , 10 , 11 Dupilumab, a monoclonal antibody that targets type 2 helper T-cell (Th2) cytokines, inhibits both IL-4 and IL-13 signaling pathways, decreasing subsequent effector cell function. 3 Only three previous studies have reported the treatment of seven patients with CAD with dupilumab, 4–6 as shown in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“… 4–6 , 10 , 11 Dupilumab, a monoclonal antibody that targets type 2 helper T-cell (Th2) cytokines, inhibits both IL-4 and IL-13 signaling pathways, decreasing subsequent effector cell function. 3 Only three previous studies have reported the treatment of seven patients with CAD with dupilumab, 4–6 as shown in Table 1 . All patients had failed to respond sufficiently to at least one line of previous therapy, such as topical corticosteroids, methotrexate, mycophenolate mofetil, azathioprine, hydroxychloroquine, apremilast, and cyclosporine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation